2023
DOI: 10.1007/s13399-023-03949-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of Ascophyllum nodosum, Arthrospira platensis extracts and calcium phosphite as therapeutic nutrients for enhancing immune response in pepper plant against Fusarium wilt disease

Abstract: The search for active inducers against diseases in the formula of therapeutic nutrients has become a necessity for many researchers. The study’s chief purpose was to make agronomic farming simpler by applying newly created therapeutic nutrients. The novelty of this research is the applied of algal extracts in adding to minerals as therapeutic nutrion. Calcium (Maxifos Ca), Ascophyllum nodosum (Greencal), and Arthrospira platensis (A. platensis), were tested for induction pepper plant resistance against Fusariu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…Our results revealed that iron oxide nanocomposites are promising for improving the growth and flowering of Gardenia jasminoides which agreement with heavily studies that stated that NPs enhanced the plant growth and production when compared with the control (Attia et al, 2023;. The synthesized Fe2O3NPs-HA enhanced the mobilization of the nutrient element (iron) and the special structure of Fe2O3NPs-HA could protect and prolong soil enzyme activity (Mousa et al, 2021), soil organic matter, soil…”
Section: Iron Content (Ppm)supporting
confidence: 89%
“…Our results revealed that iron oxide nanocomposites are promising for improving the growth and flowering of Gardenia jasminoides which agreement with heavily studies that stated that NPs enhanced the plant growth and production when compared with the control (Attia et al, 2023;. The synthesized Fe2O3NPs-HA enhanced the mobilization of the nutrient element (iron) and the special structure of Fe2O3NPs-HA could protect and prolong soil enzyme activity (Mousa et al, 2021), soil organic matter, soil…”
Section: Iron Content (Ppm)supporting
confidence: 89%
“…Severe crop losses result from the plant’s exposure to biotic and abiotic stressors. Among the most dangerous plant diseases is a fungal infection which can cause crops to entirely or partially fail and reduce crop quality, endangering the safety of the world’s food supply [ 4 , 5 ]. There are numerous methods of managing plant diseases, including chemically through synthetic pesticides, biologically using beneficial microorganisms, agriculturally using processes, and genetically [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to fungicides, natural management of Fusarium wilt uses biotic agents that have the potential for reducing the deleterious effects of the disease on crops . Therapeutic feeding is a nutrition that consists of providing nutrients and fertilizers to the plant that activate and stimulate physiological processes and help increase the plant's ability to confront challenges and hazards, as well as minimize some diseases or side effects linked with those diseases (Attia et al, 2023).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%